- Perancangan Sistem Informasi Menggunakan Kerangka Kerja TOGAF di Fitness Center - Andry, Johanes Fernandes; Jonathan, Eric - (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Sports currently have a huge impact on human life, especially in the health sector. There are many gyms spread throughout Indonesia, one of which is a fitness center located in Bandung. It has 2 branches, the first in the Metro Indah Mall shopping center, and the Bandung Electronic Center (BEC). This fitness center has implemented several applications such as Microsoft office, use of social media, and websites. However, the implementation of this business is still not optimal, it is necessary to develop company information system technology that is in line with the fitness center business. The development of this technology is based on information system architecture which produces a blueprint for the company and is assisted by an architectural framework using TOGAF (The Open Group Architecture Framework). The TOGAF framework was chosen because this framework can help analyze company needs. Apart from that, this framework has an information system architecture method. By observing the company and conducting interviews, the required business process data is obtained. So the aim of this research is to obtain the results of this blueprint design which can adjust business processes in fitness centers and can help the company's performance process so that its vision and mission can be achieved